KONSEP LENIENCY PROGRAMME DALAM KARTEL (ANALISIS PERATURAN KARTEL DI INDONESIA DAN INDIA) - Wulanda, Safira; Suherman, Suherman (Esensi Hukum, 2023)
This study aims to implement the Leniency Programme in Indonesia and assist the Business Competition Supervisory Commission as a consideration in seeking the concept of Leniency Programme if regulations regarding the Leniency Programme in Indonesia already exist. The Leniency Programme is a program to provide cartelists who dare to divulge the cartels they participate in. The reduction of the sentence can be in the form of a full amnesty and a reduction in fines. The research method used is a qualitative method with normative empirical law research and comparative law. The data search technique is through library research and interviews with the Head of the Legal Bureau of the Competition Commission in Indonesia. In this research, technique is used in content analysis. The scope of this research is done by means of comparative law. This study compares Law no. 5 of 1999 with the India Competition Act 2002 regarding the differences in the evidence of cartel practice in Indonesia carried out by the Business Competition Supervisory Commission and as in India, the Competition Commission of India (CCI) whose task is to eradicate cartel practice. The results of this study found that actually the Leniency Programme was already in the Bill of Law Number 5 of 1999, but the bill was removed from the Prolegnas. In addition, the concept of the Leniency Programme in India can be used as an example of its application in Indonesia because the business competition authorities in India and Indonesia have similarities in providing sanctions against cartels, namely administrative sanctions.